ANALISIS KUALITAS PELAYANAN PUBLIK PADA KANTOR KECAMATAN BUNGO DANI KABUPATEN BUNGO - Yunita Sari; H.M. Chotib; Joko Susanto; Zepa Anggrain; Joko Sunaryo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The quality of public services is an effort to fulfill everything related to production, services, people, processes, the environment and the needs and desires of consumers in the form of goods and services that are expected to meet the expectations and satisfaction of the community as customers. The purpose of this research is to determine the quality of public services, obstacles, and efforts at the Bungo Dani District Office, Bungo Regency. The research method used is a descriptive method with a qualitative approach. Research data collection techniques with observation, interviews, and documentation with informants totaling 15 people. The results showed that the quality of public services at the Bungo Dani District Office, Bungo Regency, had been applied to the dimensions of Reliability, Responsiveness, and Assurance. However, on the Tangible and Empathy dimensions, there are still indicators that have not been implemented, including the inconvenience of the service place including incomplete facilities and infrastructure and the unfriendliness of the employees in the service process. The inhibiting factors for the implementation of public services at the Bungo Dani District Office are internal and external factors. The internal factor is that the Camat is rarely available in the morning when the community is doing services and asks for legality or the initials of the Bungo Dani Camat. External factors, that is, people who do not carry the PBB payment sign when they want to perform services at the Bungo Dani District Office. Efforts are being made to overcome obstacles to the quality of public services at the Bungo Dani District Office by informing people who are in the process of serving with the Camat in the future to come to the Bungo Dani District Office during the day or from 10.00 am, because if it is too early the Camat there is still work to be done. Make notes at the service counter and borrow PBB from close relatives or have a clear reason if the community does not bring PBB.